ANALYSIS BUSINESS DEVELOPMENT STRATEGY AT PT. GOTO GOJEK TOKEPEDIA, TBK. FOR LONG-TERM GROWTH POST IPO - Rico Nur Ilham; Amru Usman; Wahyuddin; Tarmizi Abbas; Muttaqien (PT. Radja Intercontinental Publishing, 2025)
Startups that are growing quickly have an impact on the Indonesian economy. Due to its high degree of excitement, Indonesia is one of the five nations with the most startups. One of them is PT. Please visit Gojek Tokopedia (GOTO). Leading an IPO on the Indonesia Stock Exchange (IDX) is one of the decisions made by GoTo to collect funding or operational capital for the firm. The capital cycle, clearly, cannot be detached from the systems chosen by the organization. Internal and external environment analyses are the two components of corporate growth plans. This study employed the descriptive qualitative approach, and the methodology of data collection entailed reading evaluations of scientific literature.